PARIWISATA KERAKYATAN (COMMUNITY BASED TOURISM) DAN PENGARUHNYA PADA KESEJAHTERAAN PETANI DI DESA BUDAYA KERTALANGU KOTA DENPASAR - Pratiwi, L,PT. Kirana; Sutjipta, N; AP, IG. Setiawan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT Community Based Tourism and Its Impacts to the Welfare of Farmers in Kertalangu Culture Village, Denpasar City The development of tourism in Bali until now has oriented in the mass tourism concept that was dominated by investors through the development of large scale facilities to boost the local revenue. In the short term, tourism gives significant benefits to economic, but in the long run it will become a boomerang for economy. An alternative to the tourism problem is the establishment of community based tourism which farmers as the subject directly involve in tourism. The purpose of this research is to analyze the influence of tourism, empowerment, and participation on increasing the welfare of farmers. The study had taken in Subak Padanggalak, Kertalangu Culture Village. The sample has done with purposive sampling which consist of 57 farmers. Technique analysis data using Partial Least Square (PLS) with Smart PLS program. The research results show that tourism potential has significant impact on farmers empowerment, and it has followed by farmers empowerment also have significant impact on the farmer participation. In contrast, farmer’s participation have not significant on increasing their welfare. This indicate that the farmer’s participation have not give opimal benefit in supporting welfare of their life. Farmer have not look as the tourism subject. The role of farmers and subak have limited to support the tourism development, which the farmers have not involvement directly. It suggested the need that will be supported by private sector to develop agriculture to agrotourism. Trough the development of agrotourism a lot of agriculture commodities can be developed, and has been undertaken by various manufacturing agriculture products. The government through relevant agencies is expected to provide capital access and market acces as well as various guidance in managing agricultural products as a tourism product, thus farmer having high competitiveness on skill enhancement and improving their well-being. Keywords: Community Based Tourism, Tourism Potential, Empowerment, Participation, the Welfare of Farmers.